2008
DOI: 10.1523/jneurosci.0078-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Controlling Midline Crossing by Precerebellar Neurons

Abstract: Precerebellar neurons of the inferior olive (IO) and lateral reticular nucleus (LRN) migrate tangentially from the rhombic lip toward the floor plate following parallel pathways. This process is thought to involve netrin-1 attraction. However, whereas the cell bodies of LRN neurons cross the midline, IO neurons are unable to do so. In many systems and species, axon guidance and cell migration at the midline are controlled by Slits and their receptor Robos. We showed previously that precerebellar axons and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 57 publications
1
63
2
Order By: Relevance
“…A similar result has been reported for axons of precerebellar neurons of the inferior olive. These axons normally cross the hindbrain floor plate, are prevented from crossing in the Robo3 mutant, and are not rescued in Robo1/2/3 mutants (Di Meglio et al, 2008). Hence, there must be additional mechanisms by which Robo3 allows midline crossing.…”
Section: Existence Of Another Slit Receptormentioning
confidence: 99%
“…A similar result has been reported for axons of precerebellar neurons of the inferior olive. These axons normally cross the hindbrain floor plate, are prevented from crossing in the Robo3 mutant, and are not rescued in Robo1/2/3 mutants (Di Meglio et al, 2008). Hence, there must be additional mechanisms by which Robo3 allows midline crossing.…”
Section: Existence Of Another Slit Receptormentioning
confidence: 99%
“…The mossy-fibre-projecting precerebellar neurons (PCN) migrate marginally beneath the pial surface of the hindbrain, forming two streams: the anteroventrally directed anterior extramural stream (AES); and the ventrally directed posterior extramural stream (PES). Although the ventral directions of the AES/PES have been attributed to the Netrin and SLIT/ROBO families (Serafini et al, 1996;Yee et al, 1999;Alcantara et al, 2000;Taniguchi et al, 2002;Marillat et al, 2004;Di Meglio et al, 2008), the mechanisms that control the marginal positioning of AES/PES cells, as well as the anterior direction of the AES, are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…SLIT2 encodes a ligand of the ROBO family of axonal guidance receptors of which the dyslexia candidate ROBO1 is a member. 86,126 In the study by Igo et al, 26 linkage with 'single word reading efficiency' was reported for marker ATA5A09 on 13q12.3 (Table 1). ATA5A09 is located within the HMGB1 gene (http://www.ensembl.org/homo_ sapiens).…”
mentioning
confidence: 95%
“…86,126 As shown and described in more detail in (the legend of) Figure 2, the rate and direction of outgrowth is critically dependent on the exact receptor composition in the plasma membrane. As they have fibronectin type III domains very similar to those of the DCC receptor protein (http://www.…”
mentioning
confidence: 96%
See 1 more Smart Citation